1999
DOI: 10.1029/1998ja900100
|View full text |Cite
|
Sign up to set email alerts
|

A study of omega bands and Ps6 pulsations on the ground, at low altitude and at geostationary orbit

Abstract: Abstract. We investigate the electrodynamic coupling between auroral omega bands and the inner magnetosphere. The goal of this study is to determine the features to which omega bands map in the magnetosphere. To establish the auroralmagnetosphere connection, we appeal to the case study analysis of the data rich

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 10 publications
2
37
0
Order By: Relevance
“…Using one of the Tsyganenko magnetic field models, Tagirov (1993) has shown that the auroral torches are magnetically linked to the equatorial plane of the magnetosphere to a distance of 5-6 R E , which is consistent with the result derived by Steen et al (1988). Jorgensen et al (1999) also concluded that omega bands are the electrodynamic signature of a corrugated inner edge of a current sheet in the near-Earth (geostationary) magnetosphere. A different location of the -band and source in the magnetosphere was reported by Pulkkinen et al (1991).…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…Using one of the Tsyganenko magnetic field models, Tagirov (1993) has shown that the auroral torches are magnetically linked to the equatorial plane of the magnetosphere to a distance of 5-6 R E , which is consistent with the result derived by Steen et al (1988). Jorgensen et al (1999) also concluded that omega bands are the electrodynamic signature of a corrugated inner edge of a current sheet in the near-Earth (geostationary) magnetosphere. A different location of the -band and source in the magnetosphere was reported by Pulkkinen et al (1991).…”
Section: Introductionsupporting
confidence: 77%
“…Later, on the basis of results obtained with simultaneous multi-instrument observations, André and Baumjohann (1982), Opgenoorth et al (1983), and Steen et al (1988) showed that the -bands and the positive spikes in the D-or Y-component (Ps6 pulsations) may be regarded as the same phenomenon seen by different instruments. This led some investigators to identify -bands by means of groundbased magnetometer data, even when optical images were not available (Lühr and Schlegel, 1994;Jorgensen et al, 1999;Wild et al, 2000) or have too a low spatial resolution as a result of being taken from high altitudes (Connors and Rostoker, 1993). In accordance with early results, one of the morphological features of the Ps6 is their association with magnetospheric substorms (Saito, 1978).…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations